Involvement of L-Type Calcium Channel and SERCA2a in Myocardial Dysfunction Induced by Obesity - Leopoldo, Andre Soares [UNESP]; Lima-Leopoldo, Ana Paula [UNESP]; Sugizaki, Mario Mateus [UNESP]; Do Nascimento, Andre Ferreira [UNESP]; Salome de Campos, Dijon Henrique [UNESP]; Melo Luvizotto, Renata de Azevedo [UNESP]; Castardeli, Edson; Barnabe Alves, Carlos Augusto [UNESP]; Brum, Patricia Chakur; Cicogna, Antonio Carlos [UNESP] (Wiley-Blackwell, 2011)
Obesity has been shown to impair myocardial performance. Nevertheless, the mechanisms underlying the participation of calcium (Ca2+) handling on cardiac dysfunction in obesity models remain unknown. L-type Ca2+ channels and sarcoplasmic reticulum (SR) Ca2+-ATPase (SERCA2a), may contribute to the cardiac dysfunction induced by obesity. The purpose of this study was to investigate whether myocardial dysfunction in obese rats is related to decreased activity and/or expression of L-type Ca2+ channels and SERCA2a. Male 30-day-old Wistar rats were fed standard (C) and alternately four palatable high-fat diets (Ob) for 15 weeks. Obesity was determined by adiposity index and comorbidities were evaluated. Myocardial function was evaluated in isolated left ventricle papillary muscles under basal conditions and after inotropic and lusitropic maneuvers. L-type Ca2+ channels and SERCA2a activity were determined using specific blockers, while changes in the amount of channels were evaluated by Western blot analysis. Phospholamban (PLB) protein expression and the SERCA2a/PLB ratio were also determined. Compared with C rats, the Ob rats had increased body fat, adiposity index and several comorbidities. The Ob muscles developed similar baseline data, but myocardial responsiveness to post-rest contraction stimulus and increased extracellular Ca2+ was compromised. The diltiazem promoted higher inhibition on developed tension in obese rats. In addition, there were no changes in the L-type Ca2+ channel protein content and SERCA2a behavior (activity and expression). In conclusion, the myocardial dysfunction caused by obesity is related to L-type Ca2+ channel activity impairment without significant changes in SERCA2a expression and function as well as L-type Ca2+ protein levels. J. Cell. Physiol. 226: 2934-2942, 2011. (C) 2011 Wiley-Liss, Inc.